Contribution of a virtual magic camp to enhancing self-esteem in children with ADHD: A pilot study - Hon K. Yuen; Kevin Spencer; Kimberly Kirklin; Lauren Edwards; Gavin R. Jenkins (Health Psychology Research)
# Background